1993
DOI: 10.1093/nar/21.11.2715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis offra-2 gene expression

Abstract: We have analyzed the transcriptional regulation of the fra-2 gene in chicken embryo fibroblasts. Like c-fos, fra-2 was inducible by phorbol ester, cAMP and calcium ionophore, as well as serum. In all three cases, the induction of two species of fra-2 transcript (5.7 kb and 6.8 kb) was delayed and prolonged compared with that of c-fos mRNA. The size difference between the two transcripts was attributable to the heterogeneity of the 3'-end, probably reflecting utilization of different polyadenylation sites. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Our results demonstrate that treatment with CsA and the specific inhibition of NFATc1 by siRNA increase the expression of Fra-2. Analysis of the fra-2 promoter [59] by a Transcription Element Search System (TESS) program [60] identified three potential NFAT consensus sequences. NFAT binding to these sites could be responsible for the negative regulation of fra-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that treatment with CsA and the specific inhibition of NFATc1 by siRNA increase the expression of Fra-2. Analysis of the fra-2 promoter [59] by a Transcription Element Search System (TESS) program [60] identified three potential NFAT consensus sequences. NFAT binding to these sites could be responsible for the negative regulation of fra-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…1A). The Fra-2 promoter represents a good candidate for a Fra-2 target in vivo because it contains two AP-1 sites that interact with a Fra-2-containing AP-1 complex (10,50). Based on in vitro evidence (28), these sites have been proposed to mediate an autoregulatory Fra-2 transcriptional loop.…”
Section: Functional Characterization Of the Truncated Fra-2 Moietymentioning
confidence: 99%
“…First, fra-2 expression is turned on by second messengers, including cyclic AMP (cAMP) (1,37) and Ca 2ϩ (24). Second, the ensuing response is rather protracted (1,45), albeit less so than the one displayed by the fra-1 gene (50). Third, Fra-2 protein is modified extensively, primarily through extracellular signal-regulated kinase/mitogen-activated protein kinase (MAPK) phosphorylation (7,11,28,30).…”
mentioning
confidence: 99%
“…Transfection e ciency was normalized on the basis of b-galactosidase activity (Gorman et al, 1982;Yoshida et al, 1993). The 14 C radioactivity in the spots on TLC plates was quantitated by an image analyser (Fuji BAS 2000).…”
Section: Transfection and Cat Analysismentioning
confidence: 99%
“…By DNA sequence analysis of the fra-2 promoter region, enhancer consensus sequences such as SCM (sis conditioned medium response element, or SIE (sis inducible element)), SRE (serum response element), GC boxes and a CRE (cAMP response element)-like sequence were detected upstream of the TATA-like sequence in the same order as that in the 5'-upstream region of the chicken c-fos gene (Yoshida et al, 1993). Transient expression experiments in CEF using a series of promoter deletion constructs positioned upstream of the chloramphenicol acetyl transferase (CAT) reporter gene indicated that two typical AP-1 binding sequences, which are located between the major transcriptional initiation site and the coding sequence, and the CRE-like sequence are the major enhancers responsible for the fra-2 induction by serum (Sonobe et al, 1995).…”
Section: Introductionmentioning
confidence: 99%